Rancang Bangun Sistem Informasi Pengadaan dan Pengeluaran Perlengkapan Sekolah di SMK Al-Amah Cimanggung - Abdurrohman, Husen; Mu’minin, Ayi Mi’razul (Jurnal Dimamu, 2024)
The design of a procurement and expenditure information system is a system created to facilitate school administrators, especially the infrastructure section in carrying out the supply and expenditure of goods for all purposes in supporting learning activities. The process of procuring and dispensing equipment that is currently running at SMK Al Amah Cimanggung is still being done by hand in a book, so this process is quite time-consuming as well as the possibility of loss or damage to data on procurement and expenditure of equipment can be said to be quite likely to be lost or damaged. This research uses the OOAD (Object oriented analysis design) method with the RUP model consisting of stages: Inception, elaboration, construction, transition. UML (Unified Modeling Language) devices use Use Case, Flow of Event, Activity Diagram, Sequence Diagram, Class Diagram. The results showed that this information system can make it easier for schools, especially the facilities department that manages the procurement and expenditure of equipment to be optimal when carrying out their duties.